1998
DOI: 10.1159/000056422
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for the Treatment of Trigeminal Neuralgia

Abstract: One hundred and ten patients with trigeminal neuralgia were treated with the Gamma Knife using a single isocenter, the 4 mm secondary collimator helmet and a radiosurgical dose maximum of 70 or 80-Gy. The isocenter was placed at the trigeminal sensory root adjacent to the pons as identified on stereotactic MRI scans. Follow-up periods range from 4–49 months (mean 19.8 months). Initial pain relief was achieved in 95.5% of patients with typical trigeminal neuralgia symptoms, who had not had prior surgical interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 8 publications
3
88
2
1
Order By: Relevance
“…16 The initial response rates in our patients are comparable to those reported in the majority of previous studies of GKS. [4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16 The initial response rates in our patients are comparable to those reported in the majority of previous studies of GKS. [4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery.…”
Section: Discussionsupporting
confidence: 91%
“…8,16 Numerous authors have reported on SRS with the GK, and outcome and complication rates have been variable. [1][2][3][4][5][6]8,[10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The observed variation in success rates in the literature may be explained by the subjectivity of assessing pain (which is the most important outcome parameter in these studies), the multifactorial causes of TN (idiopathic or secondary to a pathological entity), the significantly varying stereotactic radiosurgical treatment protocols (different anatomical targets and different radiation doses), and the usage of illdefined and widely variable outcome assessment criteria.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that age is not a prognostic factor with "reasonable agreement". In spite of female gender seems to be slightly more frequent in the series (Brisman , 2004;Longhi , 2007;Pollock, 2002;), concerning pain outcome it has been systematically communicated that this variable has not prognostic significance (Aubuchon, 2010;Azar, 2009;Brisman , 2004;Dellaretti, 2008;;Hayashi, 2009;Kimball, 2010;Longhi, 2007;Massager 2007aPark, 2011Riesenburger, 2010;;Rogers, 2000;Sheehan, 2005;Tawk, 2005;Young, 1998): There was found "Consistent agreement" indicating that gender is not a prognostic variable for pain control.…”
Section: Clinical Variablesmentioning
confidence: 96%
“…Han (Han, 2009), Sheehan (Sheehan, 2005), Regis (Regís, 2006) and Towk (Tawk, 2005) conversely described worse results in younger patients. In spite of these controversial results, the majority of authors have not found significant influence of the patient age in pain control (Aubuchon, 2010;Azar, 2009;Brisman, 2004;Dellaretti, 2008;Hayashi, 2009;Little, 2008;Longhi, 2007;Massager, 2007a;Park, 2011;Petit, 2003;Riesenburger, 2010;Rogers, 2000;Young, 1998). It seems that age is not a prognostic factor with "reasonable agreement".…”
Section: Clinical Variablesmentioning
confidence: 99%
“…For cases in which conservative treatment is not successful, invasive treatment can be considered. The available options include surgical microvascular decompression (MVD) (6,7), surgical sectioning of a porrtion of the sensory component of the trigeminal nerve, stereotactic radiation therapy or gamma knife treatment (8), percutaneous balloon microcompression (9), percurtaneous glycerol rhizolysis (10), and percutaneous raodiofrequency (RF) thermocoagulation of the Gasserian ganglion (11). In addition to the operative risks inherent in surgical techniques, all neurodestructive methods present risks of sensory loss, dysesthesia, anesthesia dolorosa, corneal anesthesia, and facial muscle weakness (12,13).…”
Section: Introductionmentioning
confidence: 99%